Selective Adsorption of Propene over Propane on Hierarchical Zeolite ZSM-58 - Selzer, Carolin; Werner, Anja; Kaskel, Stefan (Industrial & Engineering Chemistry Research, 2018)
Hierarchical zeolite ZSM-58 was synthesized via a bottom-up synthesis method using varying amounts of carbon nanotubes (CNTs) as mesopore-generating template. Resulting ZSM-58 samples were analyzed by X-ray powder diffraction, scanning electron microscopy and physisorption experiments with argon, propane and propene. The adsorption of a binary propane/propene mixture was determined by breakthrough experiments. Furthermore, thermal response measurements using InfraSORP technology were applied to investigate the kinetics of propene adsorption on microporous vs hierarchical ZSM-58 samples. The use of up to 5 wt % CNTs as secondary template in the synthesis gel results in formation of zeolite ZSM-58 with mesopore volumes up to 0.06 cm3 g-1, while maintaining a high degree of crystallinity as demonstrated via X-ray powder diffraction. A direct correlation between the relative mesopore volume (Vmeso/Vtotal) and the mass fraction of CNTs applied during zeolite synthesis was found. The enhanced adsorption rates of hierarchical zeolite materials are evidenced by InfraSORP measurements with propene. Microporous and hierarchical ZSM-58 materials exhibit comparable propene adsorption isotherms at 298 K, demonstrating that the additional mesoporosity does not affect their capacity for propene. However, it promotes propane adsorption, as attributed to the higher propane capacity observed for hierarchical ZSM-58 samples with higher mesopore volume. Nevertheless, a total separation of propane/propene mixtures could be achieved for all microporous and hierarchical materials due to kinetic hindrance of propane adsorption, as confirmed by breakthrough experiments. The highly variable synthesis method allows preparation of hierarchical ZSM-58 with tailored adsorption properties. Therefore, these materials are promising candidates for industrial gas separation processes.
CRIS-Team Scopus Importer:2022-04-14